2022
DOI: 10.1021/acsami.2c10594
|View full text |Cite
|
Sign up to set email alerts
|

Metal–Organic Framework Accelerated One-Step Capture and Reduction of Palladium to Catalytically Active Nanoparticles

Abstract: Recovery of noble metals and in situ transforming to functional materials hold great promise in the sustainability of natural resources but remain as a challenge. Herein, the variable chemical microenvironments created by the inorganic−organic hybrid composition of metal−organic frameworks (MOFs) were exploited to tune the metal−support interactions, thus establishing an integrated strategy for recovering and reducing palladium (Pd). Assisted by sonic waves and alcoholic solvent, selective capture of Pd(II) fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 65 publications
0
5
0
Order By: Relevance
“…[102,120] Zr-based MOFs can also been applied for the capture and in situ reduction of metal cations. Li et al [181] synthesized UiO-66 that selectively captured Pd(II) ions and reduced them into Pd nanoparticles in situ that were uniformly distributed in the MOF support within 5 min without any extra reductant or capping agent. The as-synthesized Pd@UiO-66 demonstrated catalytic ability toward Suzuki cross-coupling reactions.…”
Section: Organic Framework (Mofs and Cofs)mentioning
confidence: 99%
“…[102,120] Zr-based MOFs can also been applied for the capture and in situ reduction of metal cations. Li et al [181] synthesized UiO-66 that selectively captured Pd(II) ions and reduced them into Pd nanoparticles in situ that were uniformly distributed in the MOF support within 5 min without any extra reductant or capping agent. The as-synthesized Pd@UiO-66 demonstrated catalytic ability toward Suzuki cross-coupling reactions.…”
Section: Organic Framework (Mofs and Cofs)mentioning
confidence: 99%
“…As excellent adsorbents, porous MOFs have made great progress in stabilizing and dispersing Pd NPs. Porous MOFs can provide excellent confinement effect for the controllable growth and restriction of further aggregation of metal NPs . Therefore, MOFs have been recognized as ideal host matrices to encapsulate Pd NPs.…”
Section: Introductionmentioning
confidence: 99%
“…In order to reduce the agglutination of metal NPs, scientists found that porous materials, including silica, molecule sieve, porous organic polymers, covalent organic frameworks, and metal−organic frameworks (MOFs), 8−13 can provide more active sites to fix firmly metal NPs into their pores and reduce the aggregation of metal NPs. 14,15 Among above porous materials, MOFs have been investigated deeply by chemists and they have become an excellent support for the loading efficiently of Pd NPs. Meanwhile, many powerful methods of loading Pd NPs have been designed by chemists.…”
Section: Introductionmentioning
confidence: 99%
“…Among the different noble MNPs, zero-valent Pd nanoparticles (Pd NPs) exhibit an excellent catalytic capability for the reduction of 4-nitrophenol (4-NP) to 4-aminophenol (4-AP). , However, due to their high surface energies, Pd NPs are prone to aggregate into larger particles, so it is difficult to control their size within a suitable range. In order to reduce the agglutination of metal NPs, scientists found that porous materials, including silica, molecule sieve, porous organic polymers, covalent organic frameworks, and metal–organic frameworks (MOFs), can provide more active sites to fix firmly metal NPs into their pores and reduce the aggregation of metal NPs. , Among above porous materials, MOFs have been investigated deeply by chemists and they have become an excellent support for the loading efficiently of Pd NPs. Meanwhile, many powerful methods of loading Pd NPs have been designed by chemists.…”
Section: Introductionmentioning
confidence: 99%